Collective Memories on the 2010 European Debt Crisis - Laura Arnemann; Kai A. Konrad; Niklas Potrafke (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We examine whether collective memories on the aid&reform programs chosen to handle the 2010 European debt crisis differ between citizens from borrower and lender countries. We use new international survey data for non-experts and experts in member countries of the euro area. The results show that non-experts from borrower and lender countries remember aspects of the programs in different manners; indicating biases for assessments of how the crisis outcomes are perceived in borrower and lender countries. Nation-serving biases may well explain if the European debt crisis has reduced the sense of belonging rather than bringing European citizens closer together.
Keywords: F36; F55; H12; H87; 330; collective memories; European debt crisis; nation-serving biases; aid&reform programmes; experts